2013
DOI: 10.1108/08858621311330245
|View full text |Cite
|
Sign up to set email alerts
|

Green marketing in B2B organisations: an empirical analysis from the natural‐resource‐based view of the firm

Abstract: Purpose -Following the natural resource based view of the firm, this paper seeks to analyse the influence of a green marketing strategy on the performance of business-to-business organisations. Also, it aims to explore the role of organisational resources as drivers of proactive environmental management. Design/methodology/approach -A model based on structural equations with partial least squares analysis is used to test the hypotheses. This model was tested on a sample of 181 industrial organisations. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 96 publications
4
127
1
1
Order By: Relevance
“…However, these approaches tend to emphasize environmentally friendly product attributes and socially responsible supplier behavior as the basis of the firm's marketing messages, while focusing less on the actual value added, or potential benefits that a prospective customer may receive (c.f., Polonsky, 2011). In the industrial marketing literature, research on sustainability has thus far focused largely on "greening" the primary supply chain, or more specifically, how to reduce the environmental impacts of operations and signal to external stakeholders a commitment to environmental values (Fraj, Martínez & Matute, 2013;Sharma et al, 2010;Gupta et al, 2014). However, what still remains relatively less well understood is the role of technology suppliers in sustainable marketing (Chan et al, 2012).…”
Section: Sustainability In the Marketing Literaturementioning
confidence: 98%
“…However, these approaches tend to emphasize environmentally friendly product attributes and socially responsible supplier behavior as the basis of the firm's marketing messages, while focusing less on the actual value added, or potential benefits that a prospective customer may receive (c.f., Polonsky, 2011). In the industrial marketing literature, research on sustainability has thus far focused largely on "greening" the primary supply chain, or more specifically, how to reduce the environmental impacts of operations and signal to external stakeholders a commitment to environmental values (Fraj, Martínez & Matute, 2013;Sharma et al, 2010;Gupta et al, 2014). However, what still remains relatively less well understood is the role of technology suppliers in sustainable marketing (Chan et al, 2012).…”
Section: Sustainability In the Marketing Literaturementioning
confidence: 98%
“…Since SMS may greatly reduce a firm's pollution emissions, previous studies indicated that SMS is positively linked with environmental performance (Chen et al, ). Thus, we focus on financial performance to explore how it is influenced by SMS in order to better explain previous inconsistent findings (Chan, ; Fraj et al, ; Fraj‐Andrés et al, ; C. N. Leonidou et al, ).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…First, the few studies linking SMS with firm performance revealed mixed findings about the impact of SMS. While some literature reported a positive effect of SMS on firm performance (Chan, ; Fraj‐Andrés, Martinez‐Salinas, & Matute‐Vallejo, ), others uncovered an insignificant impact of SMS on firm performance (Fraj, Martínez, & Matute, ; C. N. Leonidou et al, ). In this case, managers may have no idea of whether building SMS makes sense.…”
Section: Introductionmentioning
confidence: 99%
“…The role of managers in the design and development of green marketing strategies through the integration of environmental values into the organizational culture has been highlighted by Fraj et al . (). Jain and Kaur () have discussed the role of government agencies, non‐government organizations, firms and individual consumers in marketing of green ideas and products.…”
Section: Literature Reviewmentioning
confidence: 99%